317. Use cases for rapid antigen-detecting tests for COVID-19 screening and surveillance: a systematic review. (15th December 2022) - Anand, Apoorva; Bigio, Jacob; MacLean, Emily; Underwood, Talya; Pai, Nitika Pant; Carmona, Sergio; Schumacher, Samuel G; Toporowski, Amy
Abstract: Background: Testing remains critical to controlling the COVID-19 pandemic. Antigen-detecting rapid diagnostic tests (Ag-RDTs), which can be used at the point of care, have the potential to increase access to COVID-19 testing, particularly in settings with limited laboratory capacity. This systematic review synthesized literature on specific use cases and performance of Ag-RDTs for detecting SARS-CoV-2, for the first comprehensive assessment of Ag-RDT use in real-world settings. Methods: We searched three databases (PubMed, EMBASE and medRxiv) up to 12 April 2021 for publications on Ag-RDT use for large-scale screening and surveillance of COVID-19, excluding studies of only presumptive COVID-19 patients. We tabulated data on the study setting, populations, type of test, diagnostic performance, and operational findings. We assessed risk of bias using QUADAS-2 and an adapted tool for prevalence studies. Results: From 4313 citations, 39 studies conducted in asymptomatic and symptomatic individuals were included. Of 39 studies, 37 (94.9%) investigated lateral flow Ag-RDTs and 2 (5.1%) investigated multiplex sandwich chemiluminescent enzyme immunoassay Ag-RDTs. Six categories of testing initiatives were identified: mass screening (n=13), targeted screening (n=11), healthcare entry testing (n=6), at-home testing (n=4), surveillance (n=4) and prevalence survey (n=1). Sensitivity and specificity values by testing category are shown in the table. Ag-RDTs were noted as convenient, easy-to-use, and low cost, with a rapid turnaround time and high user acceptability. Risk of bias was generally low or unclear across studies. Conclusion: During the first year of the COVID-19 pandemic, Ag-RDTs were used across a wide range of real-world settings for screening and surveillance of COVID-19 in both symptomatic and asymptomatic individuals. Ag-RDTs were fast and simple to run, but due to their often low sensitivity, careful consideration must be given to their implementation and interpretation. Ag-RDTs have subsequently been rolled out more broadly and recommended for COVID-19 self-testing. Disclosures: Talya Underwood, MPhil, Oncotherapeutics: Medical writing.